2015
DOI: 10.1002/ajp.22488
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopic variation in tropical forest plants for applications in primatology

Abstract: Stable isotope analysis is a promising tool for investigating primate ecology although nuanced ecological applications remain challenging, in part due to the complex nature of isotopic variability in plant-animal systems. The aim of this study is to investigate sources of carbon and nitrogen isotopic variation at the base of primate food webs that reflect aspects of primate ecology. The majority of primates inhabit tropical forest ecosystems, which are dominated by C3 vegetation. We used stable isotope ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 177 publications
(278 reference statements)
4
59
1
Order By: Relevance
“…Although we do not have estimates of fruit δ 13 C values from our study area, the values reported by Blumenthal et al. () match well with those of keratin tissue from Cuniculus and Dasyprocta in our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although we do not have estimates of fruit δ 13 C values from our study area, the values reported by Blumenthal et al. () match well with those of keratin tissue from Cuniculus and Dasyprocta in our study.…”
Section: Discussionsupporting
confidence: 87%
“…These factors may explain why our C3 leaf‐litter δ 13 C values were around 8‰ lower than those of terrestrial prey. Fruits and flowers had mean δ 13 C values of −26.5 ± 1.6‰ in a closed‐canopy tropical African forest (Blumenthal et al., ). Although we do not have estimates of fruit δ 13 C values from our study area, the values reported by Blumenthal et al.…”
Section: Discussionmentioning
confidence: 99%
“…Graham et al (2014) could show for two tropical and temperate closed canopy forest sites that isotopic fractionation in carbon is negatively related to height and light availability but positively related to humidity. The most depleted 13 C values in tropical C3 dominated forest are typically found in the forest understory where UV radiation is limited and humidity is commonly high (van der Merwe and Medina, 1991;Cerling et al, 2004;Graham et al, 2014;Oelze et al, 2014;Blumenthal et al, 2016). We found support for this…”
Section: Site Comparison Using Vegetation Baselines -The Effects Of Hsupporting
confidence: 71%
“…Food items with ≥2‰ for their 1 SD ranges of subsample isotope ratios included blueberries and Rubus parvifolius for carbon and broccoli, cabbage, cucumbers, green peppers, lettuce, onions, peanuts, and spinach for nitrogen (Table ). Blueberries and Rubus parvifolius are undergrowth plants and are likely to be affected by local conditions, such as photosynthetic environments, humidity, and canopy cover, which generate variations in the δ 13 C values of undergrowth plants . The δ 15 N values of modern vegetable crops are variable due to the use of different fertilizers (i.e., artificial vs organic), which results in the varying δ 15 N values of some plants (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In wild chimpanzee populations, dietary difference with habitat type, dietary difference with age and sex, meat eating, dietary difference between sympatric gorilla, ecological differences among populations, and seasonal dietary differences have been studied using carbon and nitrogen stable isotope analyses. In addition, there have been systematic studies on the isotopic signatures of chimpanzees' food sources . Understanding the degree of isotopic offsets in chimpanzees is essential in order to compare the isotopic ratios of a chimpanzee's tissues and food sources.…”
Section: Carbon and Nitrogen Isotopic Offset Values (As ‰) Between DImentioning
confidence: 99%